STIMULI-RESPONSIVE DRUG DELIVERY SYSTEMS: EXTENSIVE OVERVIEW - SUBRAMANIAN, JAGAN; PADHY, RUTAMBHARA; ARUN, JANA; MURTHANNAGARI, VIVEK REDDY; GNK, GANESH (International Journal of Applied Pharmaceutics, 2025)
Drug delivery systems based on stimuli-responsive materials offer a modern scientific solution to physicians who need drug release triggered by biological signals or outside influences. This review analyzes the complete developments in stimulus-responsive drug delivery system (SRDDS) throughout a decade from 2013 to 2024 by exploring their fundamental components together with their responsive action systems and therapeutic implementations. The review investigates how various stimuli, including temperature, light, ultrasound, magnetic/electric fields, and intracellular factors like pH change, redox mechanisms, enzymes, glucose levels, inflammation, and hypoxia, influence responsive systems that have the ability to respond to several stimuli. An assessment of delivery system materials takes place, including smart hydrogels, inorganic nanoparticles, biomimetic constructs, and smart polymers, along with their respective release strategies. Research outcomes from clinics imply important therapeutic benefits of responsive system for different diseases because patients receiving cancer treatment experienced 37% greater tumor response rates, while diabetes patients showed 42% fewer hypoglycemic events, and inflammatory bowel disease (IBD) patients achieved 52% better endoscopic remission results. The remarkable achievements in delivery system have been accompanied by persistent obstacles related to large-scale manufacturing, biological challenges, and translation into clinical practice. This development now incorporates three major forward directions that unite artificial intelligence (AI) designed systems with bioelectronic interfaces and biosensors used in closed-loop frameworks. The analysis shows how responsive pharmaceutical delivery systems can solve pharmaceutical issues, yet needed collaborative efforts from multiple disciplines will drive their complete medical utilization.